Cultivating Sustainable Health in the Rural Mississippi: A Need Study for Green Economic Developmental Initiatives through the SNAP-Ed program - George, Babu; Ravola, Martha (New Countryside, 2024)
This study explores the potential role of the Supplemental Nutrition Assistance Program Education (SNAP-Ed) in fostering a green economy in rural Mississippi, specifically in Adams, Claiborne, and Jefferson counties. Using a mixed-methods approach, we conducted a comprehensive needs assessment to identify the nutritional and physical activity challenges faced by elementary school-aged children in these communities. Our findings highlight critical issues, including high obesity rates, poor dietary patterns, and limited access to fresh, healthy foods. These challenges not only affect individual health but also have broader implications for community well-being and economic sustainability. We argue that SNAP-Ed interventions are uniquely positioned to address these issues while simultaneously advancing environmentally sustainable food systems. By encouraging healthy eating behaviors such as increased consumption of fruits and vegetables, SNAP-Ed can support local agricultural economies, minimize food waste, and reduce the carbon footprint associated with food production and distribution. Our recommendations emphasize the integration of community-based food initiatives into SNAP-Ed programming. Initiatives such as school gardens, farmers’ markets, and community-supported agriculture can enhance food security, promote equitable access to nutritious foods, and empower residents to participate in sustainable farming practices. These efforts have the potential to transform rural Mississippi into a model of health-driven, community-centered, and environmentally conscious economic growth.